2001
DOI: 10.1210/edrv.22.5.0444
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Thyroid Cell Proliferation by TSH and Other Factors: A Critical Evaluation of in Vitro Models

Abstract: TSH via cAMP, and various growth factors, in cooperation with insulin or IGF-I stimulate cell cycle progression and proliferation in various thyrocyte culture systems, including rat thyroid cell lines (FRTL-5, WRT, PC Cl3) and primary cultures of rat, dog, sheep and human thyroid. The available data on cell signaling cascades, cell cycle kinetics, and cell cycle-regulatory proteins are thoroughly and critically reviewed in these experimental systems. In most FRTL-5 cells, TSH (cAMP) merely acts as a priming/co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 385 publications
(202 citation statements)
references
References 250 publications
10
187
1
4
Order By: Relevance
“…This not withstanding, very little is known about the mechanisms by which RET/PTC oncogenes transform thyroid follicular cells. Model systems of thyroid follicular cells have been widely used to study growth regulation and neoplastic transformation (Kimura et al, 2001). By using PC Cl 3 cells, here we identify OPN as a major transcriptional target of RET/PTC in thyroid cells.…”
Section: Discussionmentioning
confidence: 98%
“…This not withstanding, very little is known about the mechanisms by which RET/PTC oncogenes transform thyroid follicular cells. Model systems of thyroid follicular cells have been widely used to study growth regulation and neoplastic transformation (Kimura et al, 2001). By using PC Cl 3 cells, here we identify OPN as a major transcriptional target of RET/PTC in thyroid cells.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, rat thyroid PC Cl 3 cells are routinely maintained in 5% calf serum with a mixture of six hormones, of which only TSH and insulin are required for proliferation (see Materials and methods) (Fusco et al, 1987;Medina and Santisteban, 2000;Kimura et al, 2001). Although TSH alone does not induce DNA synthesis in this cell line (Florio et al, 2001), TSH associated with insulin or a low serum concentration is mitogenic for PC Cl 3 cells (Kimura et al, 1999).…”
Section: Effects Of Tsh On Cell Cycle Regulators In Rat Thyrocytes Inmentioning
confidence: 99%
“…According to the current model, progression through G1 is determined by the sequential phosphorylation of the retinoblastoma susceptibility gene product, p105 Rb , whose phosphorylation by the cyclin D-Cdk4/6 and E-Cdk2 complexes, activates the E2F family of transcription factors (Weinberg, 1995). Studies of the TSH-dependent regulation of cell cycle progression suggested that cyclin D3 is a critical regulator of the thyroid follicular cell cycle (Kimura et al, 2001;Medina and Santisteban, 2000). Cyclin D3 is the predominant D-type cyclin in cultured thyrocytes of dogs and humans, and in the mouse thyroid in vivo (Coppee et al, 1998;Baldassarre et al, 1999;Kimura et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient Transfection with shRNA or Dominant Negative G␣ 12 and G␣ 13 Expression Vectors-To investigate the role of G␣ 12 and G␣ 13 in TSHR-mediated MAPK activation, the RNA interference technique was used (31). For this purpose, shRNA was transiently expressed via a pSuper NeoGFP expression vector (32).…”
Section: Methodsmentioning
confidence: 99%